Forecasting global progress in breast cancer control in the context of the sustainable development goals - Jagpreet Chhatwal; Catherine Duggan; Gizem S Nemutlu; Nathaniel David Mercaldo; Ethan Thayumanavan; Tiannan Zhan; Barri M Blauvelt (BMJ Global Health, 2025)
Introduction The United Nations Sustainable Development Goal (UN-SDG) 3.4 aims to reduce premature mortality from non-communicable diseases, including breast cancer, by one-third by 2030 relative to 2015. However, many countries, particularly those with lower income, appear off track. Although mortality rates are commonly used to gauge progress, mortality-to-incidence ratios (MIRs) may provide additional insight by accounting for varying incidence and the effectiveness of cancer control measures.Methods We obtained age-standardised breast cancer incidence and mortality rates for women aged 30–69 years from 2000 to 2019, covering 199 countries stratified by World Bank income groups (low, lower middle, upper middle and high) from the Institute for Health Metrics and Evaluation Global Burden of Disease (GBD) 2019 study. Using vector autoregressive time-series analyses, we modelled and forecasted income-level and county-level mortality rates and MIRs for female breast cancer from 2020 to 2030.Results From 2015 to 2030, breast cancer mortality is projected to increase by 22.8% and 7.8% in low-income and lower middle-income countries, while decreasing by 10% and 5.4% in upper middle-income and high-income countries. MIR is projected to decrease across all income groups, with the most significant reductions seen in lower income countries, highlighting incremental improvements in breast cancer control initiatives. Only nine countries, predominantly higher income, are expected to achieve the one-third mortality reduction target. Despite MIR improvements in lower income countries, substantial mortality reductions remain elusive.Conclusion Relying solely on mortality underestimates progress in breast cancer control. Although most countries are unlikely to meet the SDG 3.4 target, concurrent use of mortality and MIR provides a more nuanced understanding of screening, diagnosis and treatment advances. Integrating MIR trends into global health evaluations may better inform breast cancer prevention strategies.